Democratic theorists in conversation turns in contemporary thought - Gagnon, Jean-Paul; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
Democracy has changed considerably in recent years to the extent that our contemporary understanding differs greatly from long-held democratic values. In this collection, renowned democratic theorists from Noam Chomsky to Francis Fukuyama give their thoughts on'new democratic theory' and its implications for the study and practice of democracy.
Keywords: Science; Science; Science, general